2006
DOI: 10.1007/s10531-005-2576-4
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Plant Species Inventory of a Philippine Lowland Rain Forest and its Conservation Value

Abstract: The Philippines are one of the most important biodiveristy hotspots on earth. Due to the extraordinary rate of environmental destruction, leaving only 3% of the land with primary forest, this biodiversity is at high risk. Despite that situation information on Philippine forest vegetation is fragmentary and focused on trees. This study aimed at analysing forest remnants in the Leyte Cordillera on the Island of Leyte, and at evaluating their role as refuge to the largely destroyed lowland forest vegetation. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…One central goal in ecosystem research is to understand the linkage between species, processes within and functions of an ecosystem (Loreau et al 2001; Hooper et al 2005). The tropics are well known for their immense species richness, in particular tropical rain forests (Whitmore et al 1985; Gentry & Dodson 1987; Gentry 1988; Duivenvoorden 1994; Galeano et al 1998; Langenberger et al 2006). Species inventories include examples of the highest species richness in rain forests, at 442 vascular plant species per 0.1 ha in a Columbia (Galeano et al 1998) and 365 species in Ecuador (Gentry & Dodson 1987).…”
Section: Introductionmentioning
confidence: 99%
“…One central goal in ecosystem research is to understand the linkage between species, processes within and functions of an ecosystem (Loreau et al 2001; Hooper et al 2005). The tropics are well known for their immense species richness, in particular tropical rain forests (Whitmore et al 1985; Gentry & Dodson 1987; Gentry 1988; Duivenvoorden 1994; Galeano et al 1998; Langenberger et al 2006). Species inventories include examples of the highest species richness in rain forests, at 442 vascular plant species per 0.1 ha in a Columbia (Galeano et al 1998) and 365 species in Ecuador (Gentry & Dodson 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Although some of these studies (e.g. Duivenvoorden 1994;Langenberger et al 2006) inventoried plots and transects along edaphic and physiographic gradients, only two have inventoried and compared different vegetation types using a uniform sampling methodology throughout. Á lvarez et al (2003) reported total vascular plant counts in three 0.1-ha plots in Amazonian, Chocoan and Andean forests in Colombia.…”
Section: Introductionmentioning
confidence: 99%
“…Leyte is characterized by a rugged mountain range, the Leyte Cordillera, which runs north to south through the whole island. The island exhibits a monsoonal climate with an average annual temperature of 27.4°C and an average precipitation of 2,586 mm (Langenberger et al 2006).…”
Section: Location Of the Research Sitementioning
confidence: 99%